The Implementation of the TPS (Think-Pair-Share) Learning Model To Improve Students Critical Thinking Skills - Salim, Amalia Nabila; Disman, Disman (Faculty of Humanities, Universitas Jenderal Soedirman, 2023)
The low ability of students' critical thinking during the learning process is the driving force behind this research. This is based on observations made by researchers who found that students during learning activities were unable to explain the material being studied straightforwardly, draw conclusions, explain the material being studied, or identify assumptions. This is because students' critical thinking skills are less developed when the learning model is used. It is hoped that this study will be able to find out and get an overview to further develop the reasoning abilities in determining fifth grade elementary school students by applying the TPS (Think Pair Offer) learning model. This study used the Classroom Action Research (CAR) method developed by Kemmis and Mc Taggart, which is one used in this study. Classroom action research is research that describes the causes and effects of treatment, as well as describes what happens when the treatment is given. and describes the entire process from the beginning of the treatment to the impact of the treatment. In this study two cycles were used which were carried out in class V of elementary school. One lesson and four stages namely planning, implementing, observing, and reflecting are each cycle. The instruments used in this review are perception sheets, field notes, test questions, and documentation. This study found that students' critical thinking skills increased by 63% in cycle I, rising to 82% in cycle II, placing it in the very good category. From these results it can be seen that there was an increase of 19% from cycle I to cycle II. This shows that one of the elementary school TPS (Think Pair Share) models can improve the critical thinking skills of fifth grade students.